Analysis of fast channel blockage: revealing substrate binding in the microsecond range. Issue 14 (26th February 2015) - Bodrenko, Igor; Bajaj, Harsha; Ruggerone, Paolo; Winterhalter, Mathias; Ceccarelli, Matteo
Abstract : The effect of filtering can be taken into account within the Markov state description to obtain the "real" power density spectrum in noise analysis of ion currents. Abstract : For an antibiotic to be effective, it needs to cross the outer membrane barrier and reach the target inside the cell. Hydrophilic antibiotics, e.g. β-lactams, use porin channels to cross the outer membrane and accumulate in the periplasm. Experimental determination of antibiotic interactions with porin is performed by using electrophysiology on a single channel level by noise analysis or single event analysis methods. We report a novel framework for analyzing the ion-current noise, taking into account the corrections due to the analogous filter and the sampling procedure, with the goal of extending the time resolution to a range previously inaccessible by event analysis or by conventional noise analysis. The new method allows one to analyse fast binding events and/or the case when the single channel is not completely blocked by the substrate. We demonstrate the power of this approach by using as an example the interactions of meropenem, an antibiotic of the carbapenem family, with the OmpF porin that is considered to be one of the main pathways for antibiotics to enter Escherichia coli . The presence of meropenem in OmpF is detected by ion current blockages, and the on and off rates are estimated from the concentration dependence of the average ion current and of its power spectral density. The obtained average residence time of the antibiotic inside the channel is in the range of a few microseconds, i.e. more than 50 times smaller than the inverse cut-off frequency of the analogous filter.